Interactive transcriptome analyses of Northern Wild Rice (Zizania palustris L.) and Bipolaris oryzae show convoluted communications during the early stages of fungal brown spot development - Castell-Miller, Claudia V.; Kono, Thomas J.Y.; Ranjan, Ashish; Schlatter, Daniel C.; Samac, Deborah A.; Kimball, Jennifer A. (Frontiers in Plant Science, 2024)
Fungal diseases, caused mainly by Bipolaris spp., are past and current threats to Northern Wild Rice (NWR) grain production and germplasm preservation in both natural and cultivated settings. Genetic resistance against the pathogen is scarce.Toward expanding our understanding of the global gene communications of NWR and B. oryzae interaction, we designed an RNA sequencing study encompassing the first 12 h and 48 h of their encounter. NWR activated numerous plant recognition receptors after pathogen infection, followed by active transcriptional reprogramming of signaling mechanisms driven by Ca 2+ and its sensors, mitogenactivated protein kinase cascades, activation of an oxidative burst, as well as Deleted: + phytohormone signaling bound-mechanisms. Several transcription factors associated with plant defense were found to be expressed. Importantly, evidence of diterpenoid phytoalexins, especially phytocassane biosynthesis, among expression of other defense genes were found. In B. oryzae, predicted genes associated with pathogenicity including secreted effectors that could target plant defense mechanisms were expressed. This study uncovered the early molecular communication between the NWR-B. oryzae pathosystem, which could guide selection for allele-specific genes to boost NWR defenses, and overall aid in the development of more efficient selection methods in NWR breeding through the use of the most virulent fungal isolates.